(untitled) (Web of Teachers: Inderscience Research, 2024)
This article highlights the importance of the 4K model in modern education, according to which it embodies the four skills most in demand in the modern world: critical thinking, creativity, communication and collaboration (collaboration). These skills are universal, meaning they can be used in any field, profession or occupation. Therefore, it is important to use this model in the organization of educational processes.